Клеймо дьявола - Новикова Елена Александровна (Разрыв шаблона, 2023)
Экземпляры: ЦБ (20230511) / Инвентарный номер: 57730 / Цена: 395.60 / Сис.шифр: 84(2=411.2)6 / Авт.знак: Н 73 / ГРНТИ: 17.82.31 / ББК: 84(2=411.2)6-44